Research on young people’s sexuality in Croatia and Slovenia, 1971-2008 : A systematic overview - Švab, Alenka (Array, 2011)
A systematic overview of research on youth sexuality and its main findings in Croatia and Slovenia during the period 1971-2008 is presented. The aim was to analyze the development of a particular type of research in the two countries characterized by an absence of sexological tradition. Research studies from four decades are contextualized – taking into account specific socio-historic and ideological underpinnings – and critically assessed. Between-country similarities and differences are discussed, as well as theoretical shortcomings and methodological limitations of the reviewed research studies. This brief history of research on young people’s sexuality in Croatia and Slovenia highlights the role of international dissemination of ideas and knowledge, particularly in the context of peripheral research communities. Due to professional divisions, financial restrictions, and the absence of ties to public health and educational policies, difficulties facing interdisciplinary research on human sexuality – the subject still perceived as either trivial or controversial – seem to continue in the post-transitional period.